(3fhQ GdfHQGS Ydi SjQI GHf SjO GdfGSs - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s ((3efRd GdeDda ai GdTQbjI HMdH s)
(3ChdgG (B:s
(3GdMeO ddg GdUeO GdhGMO GdeJaVd HJMa GdfYe hGdahGFO s
(3BNQgG (B:s
(3GdJi gP HgG ef SjQI GHf GSMGb hbO QhGgG Yf RjGO Hf YHO Gddg GdHcGFI Yf GHf GSMGb hGddg CYde s
(3GdfSNI HgG MhGTs
(3cJHJ GdeNWhWI HNW ZjQ efbhW hQOFs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs